SOVEREIGN DEBT RESTRUCTURING AND “VULTURE FUNDS” - Emilia Cornelia STOICA (Challenges of the Knowledge Society, 2016)
Defining sovereign debt - debt issued or guaranteed by a public entity: central and / or regional public authorities, central banks, public institutions or enterprises - must include the risks that its management may generate, mainly the risk of default. If an medium period of time - 3-5 years – the macroeconomic growth of a state, and as the result the increase of the public revenues constantly lies below the growth of sovereign debt, these will cause an insolvability risk to cover it, and that state should proceed to restructure its debt. Financial stability of public authorities and sovereign debt occurred since the beginning of the creation of democratic states, and instruments for debt restructuring have been continuously adapted to economic and social conjuncture. Initially, states faced a necessity of funding were borrowed from foreign governments and / or large consortia bank, and when their debts had to be restructured it has been created the international institutional framework to negotiate between debtor countries and public creditors - Paris Club - and to coordinate negotiations between public authorities and major debtor consortia - London Club. In the last decade 'vulture funds' occurred, which are hedge funds acquiring from the secondary financial market debt the securities, including public debt, to a much lower share nominal value. Subsequently, vulture funds claim states issuing debt repayment at values close or equal to the face value - in this way can make a profit of more than 100% of the financial investment they made it on the secondary market. If these countries do not comply, generally being unable to honor their public debt, vultures funds act the countries in international courts, which usually prevails because vultures funds’ action is legal under current conditions.